Response of tear cytokines following intense pulsed light combined with meibomian gland expression for treating meibomian gland dysfunction-related dry eye - Yu, Haozhe; Zeng, Weizhen; Zhao, Gezheng; Hong, Jing; Feng, Yun (Frontiers in Endocrinology, 2022)
Purpose: This study compared the changes in tear inflammatory cytokine levels after intense pulsed light (IPL) combined with meibomian gland expression (MGX) (IPL group) and instant warm compresses combined with MGX (physiotherapy group) as treatments for meibomian gland dysfunction (MGD)-related dry eye disease (DED) to explore their similarities and differences in therapeutic mechanisms. Methods: This study was a post hoc analysis of a randomized controlled trial. Thirteen patients with MGD-related DED were enrolled in each group and received three treatments correspondingly with 3-week intervals. The levels of 20 tear cytokines including TNF-α, IL-6, MMP-9, CXCL8/IL-8, CXCL10/IP-10, IL-10, EGF, IL-6R, IL-1β, IFN-γ, lactoferrin, Fas Ligand, IL-17A, LT-α, S100A9, LCN2/NGAL, IL-13, IL-12/IL-23p40, Fas, and CCL11/Eotaxin were measured at baseline, before the second and third treatments, and three weeks after the third treatment. The primary outcome was the difference in cytokines levels between baseline and the last measurement, and trends were analyzed at each measurement point. Results: At the last measurement, a significant decrease was observed in all tear cytokines for both IPL and physiotherapy groups compared with baseline. The IPL group showed greater reductions in IL-6, IL-6R, IL-1β, IL-13, and CCL11/Eotaxin than the physiotherapy group. TNF-α, CXCL8/IL-8, CXCL10/IP-10, IL-10, EGF, IL-1β, IFN-γ, and Lipocalin-2/NGAL levels continued to decrease with treatment time. Important interactions were found in the changes of IL-6 and IL-13 levels, where the levels first decreased and then slightly increased in the physiotherapy group after treatment, while they continued to decrease in the IPL group. Conclusions: The mechanisms of IPL and physiotherapy in treating MGD-related DED were both associated with reducing inflammation, and the superiority of IPL could be attributed to its better inhibitory effect of inflammatory cytokines like IL-6. In addition, several cytokines were on a downward trend during treatment, suggesting that the vicious cycle of DED was suppressed.